A dance movement therapy group for depressed adult patients in a psychiatric outpatient clinic: effects of the treatment - Pylvänäinen, Päivi M.; Muotka, Joona S.; Lappalainen, Raimo (Frontiers in Psychology, 2015)
Abstract We were interested in investigating the effects of dance movement therapy (DMT) in a psychiatric outpatient clinic with patients diagnosed with depression. DMT aims to engage the patients in physical and verbal exploration of their experiences generated in movement based interaction. The assumption was that DMT, which includes both physical engagement as well as emotional and social exploration, would alleviate the mood and psychiatric symptoms. All adult patients (n = 33) included in the study received treatment as usual (TAU). 21 patients participated in a 12-session DMT group intervention, and the remaining 12 patients chose to take TAU only. The majority of the patients suffered from moderate or severe depression, recurrent and/or chronic type. The effects of the interventions were investigated after the intervention, and at 3-month follow-up. Compared to the TAU, adding DMT seemed to improve the effect of the treatment. The effect of the DMT was observable whether the patient was taking antidepressant medication or not. At follow-up, between group effect sizes (ES) were medium in favor for the DMT group (d= 0.60-0.79). In the DMT group, the within ES at the 3 months follow-up varied from 0.62 to 0.82 as compared to TAU 0.15 – 0.37. The results indicated that DMT is beneficial in the treatment of depressed patients.